Differences in morbidity and mortality in Down syndrome are related to the type of congenital heart defect. Issue 6 (22nd April 2020) - Baban, Anwar; Olivini, Nicole; Cantarutti, Nicoletta; Calì, Federica; Vitello, Carmen; Valentini, Diletta; Adorisio, Rachele; Calcagni, Giulio; Alesi, Viola; Di Mambro, Corrado; Villani, Alberto; Dallapiccola, Bruno; et al.
Abstract: Morbidity and mortality in Down syndrome (DS) are mainly related to congenital heart defects (CHDs). While CHDs with high prevalence in DS (typical CHDs), such as endocardial cushion defects, have been extensively described, little is known about the impact of less common CHDs (atypical CHDs), such as aortic coarctation and univentricular hearts. In our single‐center study, we analyzed, in observational, retrospective manner, data regarding cardiac features, surgical management, and outcomes of a cohort of DS patients. Literature review was performed to investigate previously reported studies on atypical CHDs in DS. Patients with CHDs were subclassified as having typical or atypical CHDs. Statistical analysis was performed for comparison between the groups. The study population encompassed 859 DS patients, 72.2% with CHDs, of which 4.7% were atypical. Statistical analysis showed a significant excess in multiple surgeries, all‐cause mortality and cardiac mortality in patients with atypical CHDs ( p = .0067, p = .0038, p = .0001, respectively). According to the Kaplan–Meier method, survival at 10 and 40 years was significantly higher in typical CHDs (99 and 98% vs. 91 and 84%, log rank <0.05). Among atypical CHDs, it seems that particularly multiple complex defects in univentricular physiology associate with a worse outcome. This may be due to the surgical difficulty in managing univentricular hearts with multiple defects concurring to the clinical picture or to the severity of associated defects themselves. Further studies need to address this specific issue, also considering the higher pulmonary pressures, infective complications, and potential comorbidities in DS patients.